2015
DOI: 10.1145/2719920
|View full text |Cite
|
Sign up to set email alerts
|

Text and Data Mining Techniques in Adverse Drug Reaction Detection

Abstract: We review data mining and related computer science techniques that have been studied in the area of drug safety to identify signals of adverse drug reactions from different data sources, such as spontaneous reporting databases, electronic health records, and medical literature. Development of such techniques has become more crucial for public heath, especially with the growth of data repositories that include either reports of adverse drug reactions, which require fast processing for discovering signals of adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 103 publications
0
69
0
1
Order By: Relevance
“…A comprehensive review of NLP systems used for text processing in the medical domain can be found in [8]. Prior research in finding useful health related information from social media, mainly focused on named entity extraction (NER) tasks such as discovering ADRs in relation to a drug or treatment as reported in [8].…”
Section: A Motivating Examplementioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive review of NLP systems used for text processing in the medical domain can be found in [8]. Prior research in finding useful health related information from social media, mainly focused on named entity extraction (NER) tasks such as discovering ADRs in relation to a drug or treatment as reported in [8].…”
Section: A Motivating Examplementioning
confidence: 99%
“…Prior research in finding useful health related information from social media, mainly focused on named entity extraction (NER) tasks such as discovering ADRs in relation to a drug or treatment as reported in [8]. For example, Nikfarjam et al [12] built a system, called ADRMine, using CRFs for recognising ADR mentions from social media.…”
Section: A Motivating Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Drug side-effects are effects which are secondary to the intended effects [1]. They have drawn attention of the society because they cause a large number of morbidity and fatality every year.…”
Section: Introductionmentioning
confidence: 99%
“…The movement of the market is depended on the information of the online news articles, reactions, and proceedings is turned out to be an budding theme for investigation in the field data mining and text mining [5].To establish the outcome of modern methods for text classifications are elucidated in [6] which three problems were highlighted: documents demonstration, classifier erection and classifier assessment. Therefore, generating an information structure that can signify the data, and creating a classifier that can be utilized to visualize the class label of a document with high accuracy, develops into the major issues in text categorization.…”
mentioning
confidence: 99%